(untitled) (American Economist: Journal of Economics Finance and Global Policy, 2026)
This study is devoted to the further improvement of mechanisms for supporting and stimulating enterprises through taxation, using Surkhandarya Region as a case study. The research analyzes the economic outcomes of tax benefits, preferences, and other incentive instruments granted to enterprises operating in the region. In addition, the role of the existing tax system in shaping enterprises’ investment activity, production performance, export capacity, and job creation is assessed. Based on the findings, scientific and practical recommendations are developed for improving tax incentive mechanisms effectively, taking into account the specific economic characteristics of the region. These proposals are aimed at increasing the economic activity of business entities, expanding investment flows, and supporting the sustainable economic development of Surkhandarya Region